PENGEMBANGAN MEDIA LETTER SHARING UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA INTROVERT - Afifah, Elian Iwi; Triyono, Triyono; Hotifah, Yuliati (Jurnal Kajian Bimbingan dan Konseling, 2016)
Communication skills are the most important things for teenagers. There is a leaning that the teenagers who have low communication skills can be called as someone who is introvert personality. People who are introvert personality tend to be difficult to communicate and express verbally. The purpose of developing letter sharing media is to improve communication skills of introvert student. This research is development research by adopting Borg and Gall research model. The development result showed that this product has the criteria of usefulness, feasibility, accuracy, and attractiveness and appropriate when used to facilitate students to express communication skills in writing.